2017
DOI: 10.1063/1.4985650
|View full text |Cite
|
Sign up to set email alerts
|

Electrical detection of nuclear spin-echo signals in an electron spin injection system

Abstract: We demonstrated spin echoes of nuclear spins in a spin injection device with a highly polarized spin source by nuclear magnetic resonance (NMR). Efficient spin injection into GaAs from a half-metallic spin source of Co2MnSi enabled efficient dynamic nuclear polarization (DNP) and sensitive detection of NMR signals even at a low magnetic field of ∼0.1 T and a relatively high temperature of 4.2 K. The intrinsic coherence time T2 of 69Ga nuclear spins was evaluated from the spin-echo signals. The relation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The techniques above employ angular-momentum transfer from the electron to the nuclear spin via the contact hyperfine interaction, and they have shown remarkable success in semiconductors with an s-wave conduction band, such as GaAs [10]. While both optical and electrical pumping and detection methods can achieve high levels of nuclear spin polarization and sensitivity [11][12][13][14][15], the electrical one offers greater spatial selectivity and holds promise for integration with spintronic devices [16,17]. Studies have demonstrated that nuclear spins in highly-doped GaAs semiconductors can be dynamically polarized by injecting spin-polarized electrons from an adjacent ferromagnetic contact [18][19][20], and coherent manipulation of these polarized nuclear spins has also been achieved [21].…”
Section: Introductionmentioning
confidence: 99%
“…The techniques above employ angular-momentum transfer from the electron to the nuclear spin via the contact hyperfine interaction, and they have shown remarkable success in semiconductors with an s-wave conduction band, such as GaAs [10]. While both optical and electrical pumping and detection methods can achieve high levels of nuclear spin polarization and sensitivity [11][12][13][14][15], the electrical one offers greater spatial selectivity and holds promise for integration with spintronic devices [16,17]. Studies have demonstrated that nuclear spins in highly-doped GaAs semiconductors can be dynamically polarized by injecting spin-polarized electrons from an adjacent ferromagnetic contact [18][19][20], and coherent manipulation of these polarized nuclear spins has also been achieved [21].…”
Section: Introductionmentioning
confidence: 99%
“…This interaction dramatically increases the signal intensity available for detection of the nuclear-spin states compared with pick-up-coil detection. Several methods to create and detect nuclear spins through the hyperfine interaction have been demonstrated by using optically- [1][2][3][4][5][6][7][8][9][10][11][12][13] or electrically [14][15][16][17][18][19][20][21][22][23][24][25]-created electron spins.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical spin injection using ferromagnetic electrodes as a source of electron spins is the most recent proposal for an electrical DNP [16,[18][19][20][21][22][23][24][25]. In such a system, a highly efficient spin source is essential for an effective DNP.…”
Section: Introductionmentioning
confidence: 99%